An improved Talbot method for numerical Laplace transform inversion - Dingfelder, Benedict; Weideman, J. A. C. (Numerical algorithms, 2015)
The classical Talbot method for the computation of the inverse Laplace transform is improved for the case where the transform is analytic in the complex plane except for the negative real axis. First, by using a truncated Talbot contour rather than the classical contour that goes to infinity in the left half-plane, faster convergence is achieved. Second, a control mechanism for improving numerical stability is introduced.